1998
DOI: 10.1021/bi9813072
|View full text |Cite
|
Sign up to set email alerts
|

Binding Steps of Apolipoprotein A-I with Phospholipid Monolayers:  Adsorption and Penetration

Abstract: In whole HDL particles, the arrangement of apoA-I relative to phospholipids is of crucial interest with respect to the physiological formations of HDL. We report here new data concerning the nature of the interaction of apoA-I with condensed phospholipid (PL) monolayers (phosphatidylcholine and phosphatidylserine). The use of alternative current polarography allowed the detection for the first time of different binding steps which are dependent on apoA-I concentration. At low concentration (below 10 micrograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 35 publications
(61 reference statements)
7
43
0
Order By: Relevance
“…The surface of natural chylomicrons and VLDL is stabilized by amphophilic apolipoproteins, mainly apolipoprotein B-48 for chylomicrons and apolipoproteins B-100 and E for VLDL, and apolipoproteins are the main plasma proteins that interact with PEGylated solid lipid nanoparticles (32,33). Apolipoprotein AI efficiently binds and eventually enters phospholipid monolayers (34,35). Coating with blood proteins is a promiscuous factor controlling the pharmacokinetics of nanoparticles (21,36).…”
Section: Discussionmentioning
confidence: 99%
“…The surface of natural chylomicrons and VLDL is stabilized by amphophilic apolipoproteins, mainly apolipoprotein B-48 for chylomicrons and apolipoproteins B-100 and E for VLDL, and apolipoproteins are the main plasma proteins that interact with PEGylated solid lipid nanoparticles (32,33). Apolipoprotein AI efficiently binds and eventually enters phospholipid monolayers (34,35). Coating with blood proteins is a promiscuous factor controlling the pharmacokinetics of nanoparticles (21,36).…”
Section: Discussionmentioning
confidence: 99%
“…Both the vesicle binding and the monolayer penetration of the C1 domain require, however, the presence of anionic phospholipids, indicating that nonspecific electrostatic interactions are a driving force for its initial membrane binding. A recent monolayer study has shown that the monolayer penetration of surface active proteins, such as apolipoproteins, follows a two-step mechanism in which electrostatic surface adsorption precedes the insertion of hydrophobic side chains into the hydrophobic moiety of the monolayer (45). Based on the tertiary structure and monolayer penetration properties of the isolated C1 domain, it appears that the membrane penetration of the C1 domain follows a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the phospholipid head groups can bend slightly around the sides of the helices to interact with negative charges along the polar surface of the helix, shortening the effective distance that the protein needs to cover. Such phospholipid to amphipathic helix interactions have been proposed to occur on the surface of spherical HDL particles or vesicles (36,37).…”
Section: Discussionmentioning
confidence: 99%